Metal-Regulatory Transcription Factor-1 Targeted by miR-148a-3p Is Implicated in Human Hepatocellular Carcinoma Progression - Lyu, Zhuozhen; Yang, Mingyu; Yang, Tan; Ma, Mingze; Yang, Zhen (Frontiers in Oncology, 2021)
Metal-regulatory transcription factor-1 (MTF-1) is of importance in maintaining metal homeostasis. Copper exposure considerably stimulates the proliferation of hepatocellular carcinoma (HCC) cells with enhanced MTF-1 expression. However, the underlying molecular mechanisms have not been completely elucidated. In this study, we utilized different approaches to investigate the potential role of MTF-1 involved in HCC progression. The expression levels of MTF-1 and miR-148a-3p were determined using real-time polymerase chain reaction (PCR), western blotting, and immunohistochemistry. The interaction of MTF-1 with apurinic apyrimidinic endonuclease/redox effector factor 1 (APE/Ref-1) or miR-148a-3p was determined using immunoprecipitation or dual-luciferase reporter assay, respectively. Cell viability and metastatic ability were evaluated using colony formation, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), wound scratch, and Transwell assays, and apoptotic cells were detected by flow cytometry. The biological functions of MTF-1 and miR-148a-3p were also determined using a xenograft mouse model. MTF-1 expression was upregulated in HCC cells and was associated with poor survival and recurrence. MTF-1overexpression enhanced the proliferation and metastatic potential of HCC cells. Further mechanistic analyses demonstrated that MTF-1 bound to APE/Ref-1 and that MTF-1 is a direct target of miR-148-3p, which inversely regulated MTF-1 transcription activity. MiR-148a-3p overexpression effectively inhibited HCC cell proliferation and metastasis stimulated by MTF-1, with increased apoptosis. There was a decrease in miR-148a-3p expression in exosomes isolated from the plasma of patients with HCC and HCC cell culture supernatants. Co-incubation of HCC cells with exosomes from hepatocyte-conditioned media inhibited cell migration and caused apoptosis. The in vivo study revealed slow growth of MTF-1-knockdown and miR-148a-3p-overexpressing Hep3B-derived xenografts, with reduced tumor volume and weight compared with the control group. Collectively, these findings implicate MTF-1 as a modulator of HCC tumorigenesis and progression. Selective targeting towards exosomal miR-148a-3p which might contribute to the negative regulation of MTF-1 at least partially in hepatocellular carcinoma demonstrates therapeutic benefits for patients with HCC.